Analisis Produk Penjualan dan Distribusi terhadap Kepuasan Pelanggan pada Jasa Yudistira - Erni anggriani; Rahmat Daim Harahap (LPPM IAI Nasional Laa Roiba Bogor, 2023)
This research aims to determine the effect of product quality, personal selling and distribution of satisfaction on customers at Yudhistira Publishing Services. I hope that this research will provide suggestions and recommendations to the publisher Yudistira in order to achieve the company's goals. The research method used is quantitative with survey methods and descriptive explanations. The data collection technique is a questionnaire, with size as a measuring tool. While the analytical method used is path analysis, which consists of validity tests, reliability tests, partial tests, simultaneous tests and the coefficients of determining the test. The results show that product quality has a significant effect on customer satisfaction fraction. Keywords: distribution, satisfaction, customer, product